2001
DOI: 10.1242/jcs.114.24.4587
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin-1 suppression of fibronectin-regulated cell adhesion and motility

Abstract: Fibulin-1 is an extracellular matrix protein often associated with fibronectin (FN) in vivo. In this study, the ability of fibulin-1 to modulate adhesion, spreading and motility-promoting activities of FN was investigated. Fibulin-1 was found to have pronounced inhibitory effects on the cell attachment and spreading promoted by FN. Fibulin-1 was also found to inhibit the motility of a variety of cell types on FN substrata. For example, the FN-dependent haptotactic motility of breast carcinoma (MDA MB231) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Studies have shown that FBLN1 can regulate cell morphology, adhesion, spread and promote cell movement, which is related to cancer growth, cell migration, and invasive growth [ 32 36 ]. The effect of FBLN1 as an ECM on cell migration and metastasis is complex [ 37 ]. On the one hand, the ECM is a storeroom of copious signal molecules, which can regulate various tumour-related pathological and physiological processes including tumour metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that FBLN1 can regulate cell morphology, adhesion, spread and promote cell movement, which is related to cancer growth, cell migration, and invasive growth [ 32 36 ]. The effect of FBLN1 as an ECM on cell migration and metastasis is complex [ 37 ]. On the one hand, the ECM is a storeroom of copious signal molecules, which can regulate various tumour-related pathological and physiological processes including tumour metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the composition and structure of the ECM determine the resistance and adhesion encountered by the migrating cells, thereby increasing the colonisation of tumour cells in the blood vessel wall and target organs [ 40 ]. The effect of FBLN1 on cell migration and metastasis is believed to be specific to cell and organ types [ 37 ]. Therefore, FBLN1 may be involved in regulating the various stages of BM of tumour cells, such as detachment from the primary tumour, infiltration of blood vessels, and colonisation of the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…FBLN1 is an extracellular glycoprotein that is involved in cell adhesion and motility along fibers in the extracellular matrix. 79 The SNP located in FBLN1 has been associated with the hyperthymic temperament in a genome-wide association study (GWAS) of BD, 80 which is also a risk factor for BD itself.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Controls included the (i) neutralizing antibody for each of the corresponding recombinant proteins and (ii) colony formation assay for MCF10A. With respect to the concentration of recombinant proteins, we initiated with the published approximate ranges of SLIT3 [44] and FBLN1 [45,46] followed by serial dilution experiments of 0.1, 1, and 10 µg/mL for SLIT3 and FBLN1, and 0.1 and 1 µg/mL for PENK. SLIT3 and PENK at the concentration of 10 µg/mL and 1 µg/mL, respectively, induced growth suppression.…”
Section: Slit3 Fbln1 and Penk Induce Apoptosis In Mda-mb-231mentioning
confidence: 99%